Pemanfaatan Media Pembelajaran Mencerna sebagai Implementasi Student Active Learning di Kelas 3 SD Negeri 1 Weleri - Desi Nuzulia Rosyidah; Meilan Tri Wuryani; Dian Kusumawati (Mataram University, 2026)
Indonesian language instruction in elementary school continues to rely mainly on lecture-based teaching and textbooks-centered learning, result in limited student participation. This study sought to develop MENCERNA (Interactive Narrative Story Media), explain its implementation in promoting Student Active Learning, and investigate third-grade students' responses and learning outocomes at SD Negeri 1 Weleri. This study adopted the Research and Development (R&D) approach using the 4D model, which includes the define, design, develop, and disseminate stages. Data were obtained through observations, interviews, validation questionnaires, documentation, and learning achievement tests, then analyzed using descriptive quantitative techniques and the N-Gain test. The findings indicated that MENCERNA obtained a validation score of 80% from both the material and media experts, demonstrating that it was valid for classroom implementation. Its implementation promoted active atudent involvement through observation, questioning, discussion, idea exchange, and worksheet completion. Students demonstrated positive responses toward the media, while their learning outcomes improved, with the mean pre-test score rising from 63.57 to 87.51 on the post-test, producing an N-Gain score of 0.66 (moderately effective). Therefore, MENCERNA represent an appropriate instructional medium for enhacing Student Active Learning and Indonesian language learning outcomes.